Interação mãe-criança com deficiência visual: um estudo longitudinal das habilidades sociocomunicativas infantis. - Medeiros, Carolina Silva de (2013)
The Perspective on Language and Social Interaction Scholars emphasizes that the first socially established interactions between a child and an adult are central to the development of linguistic, cognitive, social and affective skills. Studies on infant language development emphasize the presence of typical communication patterns, given that the child s age, cognitive skill and language development all influence the maternal inputs employed. For children with special needs, such as the visually impaired, interaction with the mother is likely to be of a particular kind, given that the first contact, that is, eye contact, is nonexistent. The present longitudinal study evaluated the mother-child with visual impairment interaction, and aimed to determine the degree of infant language development based on their social communication skills. Specifically, the study evaluated the communication behaviors of both mother and infant, identified scenes of joint attention within interactive episodes, and investigated the maternal conception regarding child development. Investigations were made by conducting two case studies concerning two completely blind children (three and four years old) and their mothers. Data collection was made by visiting the residence of the dyads during six distinct stages with two-month intervals between visits. Instruments employed during the study included semi-structured interviews using a digital recorder, assessment of expressive vocabulary list (LAVE), and 12 movies recorded for each dyad. During each stage, two different observational situations were employed: free play and structured. For the latter case, children were oriented to play with previously selected educational toys, suitable for both their age and visual conditions. Interviews were organized into thematic categories, as proposed by Bardin. Furthermore, 10 of the 20 minutes of video available for each situation were transcribed based on the CHAT format using CHILDES software (Child Language Data Exchange System). The CLAN program of the same software provided the necessary frequency and precision of data coding. Categories were elaborated based on the aims of the study, on observation protocols and from similar researches conducted in the field of expertise. The mother of the first dyad proposed that child development requires specific guidance, particularly regarding perceptual functions such as touch and hearing. The LAVE method detected an improvement between the first and last application. During the observations the mother was concerned about promoting child participation on the interactive process. This, in turn, led to an improved self-initiative and a contextualized use of different communication behaviors by the child. A maternal strategy concerning the attentional focus of the child, as well as the mother s report that the child s linguistic development seemed inappropriate for the age, was detected for dyad 2. This was further supported by both the LAVE and the observations, which evidenced the difficulty of the child to communicate appropriately, using decontextualized words and rigid verbal expressions. In general, the present study emphasizes the importance of considering the situational context and observing the members of the dyad by means of bidirectional perspectives, given that one s behavior influences the other. Results of the present study is expected to provide assistance for intervention programs which aim to improve the development of social communication skills by visually impaired children, via mother- child interaction.